The effects of different mechanisms on the development of post-ERCP pancreatitis in an ERCP model in rats - Süleyman BOZKURT; Ali Güner; Hüseyin KADIOĞLU; Can KEÇE; Erhan REİS and Halil COŞKUN (Turkish Journal of Gastroenterology, 2019)
-